Proliferation and regeneration of the healthy human urothelium: a multi-scale simulation approach with 16 hypotheses of cell differentiation - Siegel, Fabian; Torelli, Angelo; Mattis, Minca; Debatin, Julian; Erben, Philipp; Gumbel, Markus (PLOS ONE, 2025)
The urothelium as a stratified epithelium of the urinary tract is a slow regenerating tissue of different layers and shares similarities with the epidermis. Characteristics of its cell types, regeneration, tissue homeostasis, integrity and self organization are only partly understood. Precise computer-based models which investigate the cell kinetics of the urothelium from a theoretical perspective are beneficial for the regenerative medicine field and cancer research. Here an agent-based computer simulation based on the Glazier-Graner-Hogeweg (GGH) approach were developed and tested on 16 hypotheses of proliferation and differentiation mechanisms of the healthy urothelial tissue in steady state and tissue regeneration. A fitness-function was introduced for the quantitative comparison of respective models. The findings indicate that two similar hypotheses with the following features describe the healthy tissue best: 1) Progenitor cells either divide and differentiate in a stem cell fashion or proliferate according to the population asymmetry model in epidermis, 2) Basal cells divide symmetrically and differentiate into intermediate cells depending on contact to the basal membrane. 3) Intermediate cells do not proliferate but differentiate into umbrella cells when they are in contact with the medium.